Analisis Sistem Informasi Akuntansi Penggajian Pegawai Negeri Sipil Pada UPTD SMPN 1 Purwoasri Kabupaten Kediri - Novita, Novita; Nurdiwaty, Diah (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2017)
This research is based on the fact that Payroll Accounting Information System is one of the principal activities of accounting information system designed to handle salary and payroll calculation on employees. The problems of this research are: (1). Analyze how the organizational structure of Human Resources (HR) on the payroll system? (2). Analyze how Payroll Accounting Information System at UPTD SMPN 1 Purwoasri Kediri Regency? (3). Analyze how Payroll Accounting Information System software is used at the office UPTD SMPN 1 Purwoasri Kediri ?. This research uses descriptive qualitative approach with the aim to know the application of Civil Servant Payroll Accounting Information System (PNS) whether it is effective and efficient. Data collected by doing observation, interview, documentation, and library study with stages collect data, analyze, compare findings with theories that exist and provide conclusions and suggestions on school institutions. The result of the research shows the Human Resource Organization Structure (SDM) related to payroll system of Civil Servant (PNS) at UPTD SMPN 1 Purwoasri namely School Operator, Personnel Administration, and Finance Administration / Financing, Payroll Accounting Information System used is good enough visible documents used in the flowcharts of employee payments are in accordance with Standard Operating Procedures (SOP) Government Regulation No. 30 of 2015 on Payroll Civil Servants (PNS), and processing salaries that are no longer manual but using software payroll Garuda produce information data presented more accurate.